Hydrogen Sulfide Levels and Nuclear Factor-Erythroid 2-Related Factor 2 (NRF2) Activity Are Attenuated in the Setting of Critical Limb Ischemia (CLI) - Islam, Kazi N (J Am Heart Assoc, 2015)
BACKGROUND: Cystathionine γ-lyase, cystathionine β-synthase, and 3-mercaptopyruvate sulfurtransferase are endogenous enzymatic sources of hydrogen sulfide (H(2)S). Functions of H(2)S are mediated by several targets including ion channels and signaling proteins. Nuclear factor-erythroid 2-related factor 2 is responsible for the expression of antioxidant response element–regulated genes and is known to be upregulated by H(2)S. We examined the levels of H(2)S, H(2)S-producing enzymes, and nuclear factor-erythroid 2-related factor 2 activation status in skeletal muscle obtained from critical limb ischemia (CLI) patients. METHODS AND RESULTS: Gastrocnemius tissues were attained postamputation from human CLI and healthy control patients. We found mRNA and protein levels of cystathionine γ-lyase, cystathionine β-synthase, and 3-mercaptopyruvate sulfurtransferase were significantly decreased in skeletal muscle of CLI patients as compared to control. H(2)S and sulfane sulfur levels were significantly decreased in skeletal muscle of CLI patients. We also observed significant reductions in nuclear factor-erythroid 2-related factor 2 activation as well as antioxidant proteins, such as Cu, Zn-superoxide dismutase, catalase, and glutathione peroxidase in skeletal muscle of CLI patients. Biomarkers of oxidative stress, such as malondialdehyde and protein carbonyl formation, were significantly increased in skeletal muscle of CLI patients as compared to healthy controls. CONCLUSIONS: The data demonstrate that H(2)S bioavailability and nuclear factor-erythroid 2-related factor 2 activation are both attenuated in CLI tissues concomitant with significantly increased oxidative stress. Reductions in the activity of H(2)S-producing enzymes may contribute to the pathogenesis of CLI.